Early versus late anticoagulation for ischaemic stroke associated with atrial fibrillation: multicentre cohort study. Issue 3 (19th November 2018) - Wilson, Duncan; Ambler, Gareth; Banerjee, Gargi; Shakeshaft, Clare; Cohen, Hannah; Yousry, Tarek A; Al-Shahi Salman, Rustam; Lip, Gregory Y H; Houlden, Henry; Brown, Martin M; Muir, Keith W; Jäger, Hans Rolf; et al.
Abstract : Background and purpose: The optimal time to start oral anticoagulant (OAC) in patients with ischaemic stroke due to non-valvular atrial fibrillation (AF) is unknown. We reviewed OAC timing in relation to 90-day clinical outcomes as a post hoc analysis from a prospective multicentre observational study. Methods: We included patients with data on time to initiation of OAC from CROMIS-2 (Clinical Relevence Of Microbleeds In Stroke-2), a prospective observational inception cohort study of 1490 patients with ischaemic stroke or transient ischaemic attack (TIA) and AF treated with OAC. The primary outcome was the composite outcome of TIA, stroke (ischaemic stroke or intracranial haemorrhage) or death within 90 days of the qualifying stroke or TIA. We performed adjusted logistic regression analyses to compare early (0–4 days) and later (≥5 days or never started) OAC initiation. Results: We included 1355 patients, mean age 76 (SD 10), 580 (43%) women. OAC was started early in 358 (26%) patients and later (or not at all) in 997 (74%) patients. The event rate within 90 days was 48/997 (5%) in the late-OAC group (2 intracranial haemorrhages, 18 ischaemic strokes or TIAs and 31 deaths (three deaths were as a result of new ischaemic strokes)) versus 7/358 (2%) in the early-OAC group (5 ischaemic strokes or TIAs and 2 deaths). In adjusted analyses, late OAC was not associated with the composite outcome (adjusted OR 1.17, 95% CI 0.48 to 2.84, p=0.736). Conclusion: In adjusted analyses, early OAC after acute ischaemic stroke or TIA associated with AF was not associated with a difference in the rate of the composite outcome of stroke, TIA or death at 90 days, compared with late OAC. However, despite adjustment for important baseline factors, patients selected for early OAC and late OAC might still have differed in important respects; evaluation of OAC timing in adequately powered randomised trials is required. Clinical trial registration: NCT02513316 .